La Propiedad Industrial En La Sociedad Del Conocimiento. Tendencias Actuales - ChÃ¡vez, Eduardo Vinicio MejÃa (European Scientific Journal, ESJ, 2017)
Today humanity is immersed in the knowledge society, so that intangibles have acquired great value throughout the world. This has contributed to globalization and the emergence of economies founded on knowledge and technological development, which have led to the emergence of new intellectual products that generate industrial property rights. The ownership of these industrial property rights has determined the development and economic advancement of countries, but also an absolutely heterogeneous growth between them, as a differentiating element is contemplated, the science and technology they possess. It is therefore in permanent debate whether industrial property is a mechanism of technological development, based on economic recognition of the institutions and their inventors for the science and technology they generate, or whether it is a form of privatization of knowledge and a new Technological colonialism.